Evaluating artesunate monotherapy and dihydroartemisinin-piperaquine as potential antimalarial options for prevaccination radical cures during future malaria vaccine field efficacy trials - Alphonse Ouédraogo; Daouda Ouattara; San Maurice Ouattara; Amidou Diarra; Emilie S. Badoum; Alimatou Hema; Amidou Z. Ouédraogo; Denise Hien; Edith C. Bougouma; Issa Nébié; Valéry Bocquet; Michel Vaillant; et al. (Malaria Journal)
Abstract Background In malaria vaccine clinical trials, immune responses after vaccination may be compromised due to immunosuppression caused by concurrent Plasmodium falciparum infection. This has a direct effect on the protective efficacy of the vaccine being evaluated. Therefore, parasite clearance prior to vaccination is being considered. Drugs with good safety and efficacy profiles and a short posttreatment prophylaxis period should be used. Two antimalarial drugs, artesunate (AS) as monotherapy and dihydroartemisinin-piperaquine (DHAPQ), have been evaluated in order to identify the most suitable option for use in future trials. Methods A cohort of children aged 1.5–12 years living in the Banfora Health District area was recruited. They were randomly assigned to receive supervised curative doses of AS monotherapy for 7 days or DHAPQ for 3 days. A polymerase chain reaction (PCR) was performed 21 days after treatment to confirm clearance of infection, and only those with a negative PCR were included in the study cohort for a 6-month longitudinal follow-up. Cohort children were actively visited fortnightly to collect blood samples for P. falciparum detection via microscopy and PCR. Passive surveillance was also conducted at the local health facility to record incident malaria episodes that occurred between two active visits. Results A total of 513 children were treated. Among these patients, 458 (89.3%) were free of P. falciparum malaria infection on day 21: 87.3% (226/259) in the AS group vs 91.3% (232/254) in the DHAPQ group (p = 0.053). The mean time to first malaria infection by microscopy was 154.9 (2.9) days in the DHAPQ arm and 129.0 (3.9) days in the AS arm (p < 0.01). The incidence rates of clinical malaria episodes during the follow-up period were 0.507 (0.369–0.645) and 0.293 (0.190–0.397) in the AS and DHAPQ arms, respectively (p < 0.05). Conclusions These findings suggest that although both drugs are effective in clearing P. falciparum infections, AS is likely to cause no more than minimal interference with the evaluation of vaccine efficacy endpoints and could, therefore, be considered for use. Trial registration: NCT04601714.